Urgensi Al-Qur’an dan Hadits sebagai Basis Pendidikan Remaja dalam Menghadapi Tantangan Era Society 5.0 - Syukri, Muhammad; Rizalie, Fikri (STIT Syekh Muhammad Nafis Tabalong, 2025)
The Qur'an and Hadith are guidelines for Muslims. The issue of education is also inseparable from the auspices of the Qur'an and Hadith. Many messages conveyed in the Qur'an and Hadith are related to education, especially family education. The family as a fundamental aspect must certainly have a clear direction, so that the children produced from this institution can be born into quality individuals. Adolescence is a time when a person is easily influenced and wants freedom. Especially in today's society. Of course, the challenges faced by teenage children and their parents will be greater. So that messages from the Qur'an and Hadith are needed as guidelines in educating teenage children in the era of society. This research method uses library research with a qualitative approach. Sources related to the Qur'an, Hadith and family education are analyzed so as to form a writing that can answer the formulation of the problem in this article. The results show that the Qur'an and Hadith play a very important role in the education of adolescent children, especially for those who grow up and develop in the era of society. This is shown through the messages in the Qur'an and Hadith. These messages include how to instill faith, worship and morals in children. These messages can be used as basic guidelines for parents in educating teenage children in facing the era of society 5.0.